The Role of Entrepreneurial Orientation and Learning on the Performance of Junior Enterprises - dos Santos, Jeferson Carlin; Ribeiro da Silva, Hermes Moretti; Marcondes de Moraes, Gustavo Hermínio Salati; Cortegoso de Oliveira Frascareli, Fernanda (Organizations and Markets in Emerging Economies, 2023)
This study aims to develop a model that analyzes the influence of learning orientation (LO) and entrepreneurial orientation (EO) as antecedents of performance in junior enterprises (JEs). To this end, a research model was developed and tested through a survey of a sample of 235 presidents of Brazilian Junior Enterprises. Through the Structural Modeling Equation (SME) technique, the effects of each of the variables on the performance of JEs were evaluated. The results indicate that both the EO and LO dimensions have a positive impact on the performance of this type of a company. Therefore, this study advances the understanding of the impact of strategic dimensions in a new context, as well as making direct contributions to these companies and other interested parties to use the results presented to support the construction of new strategies for improving performance.